Resin composition, film, multilayer film, and method for producing film
A resin composition with aromatic polycarbonate, polyarylate resin, and a zinc salt of a phosphate compound addresses roll staining issues during film production, ensuring high light transmittance, low haze, and heat resistance in the film.
Patent Information
- Application Number
- JP2020192147
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-19
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-11-19
AI Technical Summary
Existing resin compositions containing aromatic polycarbonate and polyarylate resins for film production using rolls are prone to roll staining due to transesterification, which affects film quality and efficiency.
A resin composition is developed by blending 20 to 80 parts by mass of aromatic polycarbonate resin, 80 to 20 parts by mass of polyarylate resin, and a metal salt of a phosphate compound, specifically a zinc salt, to inhibit transesterification and prevent roll staining during film formation.
The solution effectively suppresses roll staining, enables high total light transmittance and low haze, and maintains excellent heat resistance in the resulting film, enhancing film production efficiency and quality.
Smart Images

Figure 0007600633000010 
Figure 0007600633000001 
Figure 0007600633000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, a film using the resin composition, a multilayer film, and a method for producing a film. In particular, the present invention relates to a film that is preferably used as a protective film or substrate for a transparent conductive film. [Background technology]
[0002] Transparent conductive films are used in film sensors of touch panels, electronic paper, dye-sensitized solar cells, touch sensors, etc. A transparent conductive film 10 is known that is composed of an electrode layer (transparent conductive film) 11, a substrate 12, an adhesive layer 13, and a protective film 14, for example, as shown in FIG. Specifically, Patent Document 1 describes a transparent conductive film laminate having an adhesive layer, a film substrate, and a transparent conductive film in this order on a protective film, in which a polycarbonate-based resin is used as the protective film. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2018-152187 A Summary of the Invention [Problem to be solved by the invention]
[0004] On the other hand, from the viewpoint of improving the heat resistance of the film, a polyarylate resin may be blended with an aromatic polycarbonate resin to produce a film. It has been found that when a film is produced using a roll from a resin composition containing such an aromatic polycarbonate resin and a polyarylate resin, stains may occur on the roll. The present invention aims to solve such problems, and to provide a resin composition that is less likely to cause roll stains when attempting to produce a film using a roll, as well as a film, a multilayer film, and a method for producing a film that use the resin composition. [Means for solving the problem]
[0005] In view of the above problems, the present inventors have conducted research and found that the above problems can be solved by blending a metal salt of a phosphate compound with an alloy of an aromatic polycarbonate resin and a polyarylate resin. Specifically, the above problems were solved by the following means. <1> A resin composition comprising 20 to 80 parts by mass of an aromatic polycarbonate resin, 80 to 20 parts by mass of a polyarylate resin, and a metal salt of a phosphate compound. <2> The composition contains 0.01 to 0.15 parts by mass of a metal salt of a phosphate compound relative to 100 parts by mass of the total of the aromatic polycarbonate resin and the polyarylate resin. <1> The resin composition according to claim 1. <3> the metal salt of a phosphate compound comprises a zinc salt of a phosphate compound; <1> or <2> The resin composition according to claim 1. <4> The metal salt of the phosphate compound includes at least one of a compound represented by formula (P1) and a compound represented by formula (P2). <1> or <2> The resin composition according to claim 1. Formula (P1) Formula (P2) [ka] (In formula (P1) and formula (P2), R x each independently represents a linear or branched alkyl group having 3 to 30 carbon atoms. <5> The metal salt of the phosphate compound includes at least one of a compound represented by formula (P1-1) and a compound represented by formula (P2-1). <1> or <2> The resin composition according to claim 1. Formula (P1-1) Formula (P2- 1 ) [ka] <6> The weight average molecular weight of the polyarylate resin is 30,000 to 55,000. <1> ~ <5> 10. The resin composition according to claim 9 . <7> The glass transition temperature of the resin composition measured by differential scanning calorimetry is 155° C. or higher. <1> ~ <6> 10. The resin composition according to claim 9 . <8> The weight average molecular weight of the aromatic polycarbonate resin is 20,000 to 38,000. <1> ~ <7> 10. The resin composition according to claim 9 . <9> <1> ~ <8> 2. A film formed from the resin composition according to claim 1. <10> The thickness is 25 to 500 μm. <9> The film according to claim 1. <11> <9> or <10> A multilayer film comprising the film according to claim 1. <12> The film has at least one layer selected from the group consisting of a hard coat layer, an anti-blocking layer, an adhesive layer, an adhesion layer, and an index matching layer on one or both sides thereof. <11> The multilayer film according to claim 1. <13> <1> ~ <8> 2. A method for producing a film, comprising extruding the resin composition according to any one of 1 to 10, and transporting the extrudate through a roll to form the film. Effect of the Invention
[0006] The present invention makes it possible to provide a resin composition that is less likely to cause roll stains when a film is produced using a roll, as well as a film, a multilayer film, and a method for producing a film that use the resin composition. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a layer structure of a transparent conductive film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values are those at 23° C. unless otherwise specified. In the description of groups (atomic groups) in this specification, when the description does not indicate whether the group is substituted or unsubstituted, the description also includes groups (atomic groups) that have a substituent as well as groups (atomic groups) that have no substituent. For example, the term "alkyl group" includes not only alkyl groups that have no substituent (unsubstituted alkyl groups), but also alkyl groups that have a substituent (substituted alkyl groups). In this specification, when the description does not indicate whether the group is substituted or unsubstituted, the description is preferably unsubstituted. The term "film" as used herein refers to a generally flat molded body having a small thickness relative to its length and width, and is intended to include a sheet. The term "film" as used herein may be either a single layer or a multilayer. In this specification, "parts by mass" indicates the relative amount of a component, and "% by mass" indicates the absolute amount of a component. In cases where the standards shown in this specification differ depending on the year and the measurement method, etc., the standards shall be those in effect at the time of filing, unless otherwise stated.
[0009] The resin composition of the present embodiment contains 20 to 80 parts by mass of an aromatic polycarbonate resin, 80 to 20 parts by mass of a polyarylate resin, and a metal salt of a phosphate compound. By blending a metal salt of a phosphate compound with such an alloy of an aromatic polycarbonate resin and a polyarylate resin, the film can be effectively prevented from being inhibited even when the film is formed using a roll. Furthermore, a film having a high total light transmittance and low haze can be obtained. Furthermore, a film having excellent heat resistance can be obtained. The reason why the contamination of the roll can be suppressed is presumed to be as follows. When aromatic polycarbonate resin is rolled into a film, the roll is hardly stained. However, it has been found that when a resin composition containing a polyarylate resin and an aromatic polycarbonate resin is formed into a film using a roll, roll staining may occur. The present inventors speculated that the roll staining is due to ester exchange between polyarylate resins, and tried to use various ester exchange inhibitors. As a result, it was speculated that the occurrence of roll staining could be suppressed by using a resin composition in which a metal salt of a phosphate compound is blended with an alloy of a polyarylate resin and an aromatic polycarbonate resin.
[0010] <Aromatic polycarbonate resin> The resin composition of the present embodiment contains an aromatic polycarbonate resin. By using an aromatic polycarbonate resin, a film having excellent transparency can be obtained. The aromatic polycarbonate resin is not particularly limited in type, etc., as long as it contains a -[OR-OCO]- structural unit (R contains at least an aromatic group and may further contain an aliphatic group, and has a linear or branched structure) containing a carbonate bond in the molecular main chain, and various aromatic polycarbonate resins can be used.
[0011] In the present embodiment, the aromatic polycarbonate resin is preferably a bisphenol-type polycarbonate resin. The bisphenol-type polycarbonate resin means that preferably 80 mol % or more, more preferably 90 mol % or more of the structural units constituting the aromatic polycarbonate resin are carbonate structural units derived from bisphenol (preferably bisphenol A) and / or its derivatives. The bisphenol type polycarbonate resin is preferably a bisphenol A type polycarbonate resin.
[0012] The weight average molecular weight of the aromatic polycarbonate resin is preferably 20,000 or more, more preferably 22,000 or more. By making it equal to or more than the lower limit, the moldability of the film tends to improve. In addition, the upper limit of the weight average molecular weight of the aromatic polycarbonate resin is preferably 38,000 or less, more preferably 35,000 or less, even more preferably 30,000 or less, and even more preferably 28,000 or less. By making it equal to or less than the upper limit, the increase in haze of the film can be effectively suppressed. The weight average molecular weight of the aromatic polycarbonate resin is measured according to the description in the Examples section described later. When the composition contains two or more types of aromatic polycarbonate resins, the weight average molecular weight is the weight average molecular weight of the mixture of aromatic polycarbonate resins (the same applies to other physical properties below, and also to other resin components).
[0013] The glass transition temperature (Tg) of the aromatic polycarbonate resin is preferably 125°C or higher, more preferably 130°C or higher, and even more preferably 135°C or higher. By making it equal to or higher than the lower limit, shrinkage during heating can be suppressed. Furthermore, the glass transition temperature (Tg) of the aromatic polycarbonate resin is not particularly limited, but is preferably 160°C or lower, more preferably 155°C or lower, even more preferably 150°C or lower, and even more preferably 145°C or lower. By making it equal to or lower than the upper limit, an increase in the haze of the film can be effectively suppressed. The glass transition temperature (Tg) of the aromatic polycarbonate resin is measured according to the description in the Examples section described later.
[0014] For details of the aromatic polycarbonate resin, reference can be made to paragraphs 0011 to 0020 of JP 2012-144604 A and paragraphs 0014 to 0035 of JP 2019-002023 A, as long as they do not deviate from the spirit of this embodiment, and the contents of these are incorporated into this specification.
[0015] <Polyarylate resin> The resin composition of the present embodiment contains a polyarylate resin. By using the polyarylate resin, a film having excellent heat resistance can be obtained. The polyarylate resin used in the present embodiment is preferably an aromatic polyester composed of structural units derived from an aromatic dicarboxylic acid and structural units derived from a bisphenol. Examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, benzophenone dicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 3,3'-diphenyldicarboxylic acid, and 4,4'-diphenylether dicarboxylic acid, and terephthalic acid and / or isophthalic acid are preferred. Examples of bisphenols include 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane, 2,2-bis(4-hydroxy-3,5-dichlorophenyl)propane, 4,4'-dihydroxydiphenylsulfone, 4,4'-dihydroxydiphenylether, 4,4'-dihydroxydiphenylsulfide, 4,4'-dihydroxydiphenylketone, 4,4'-dihydroxydiphenylmethane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, and the like. Of these, 2,2-bis(4-hydroxyphenyl)propane (bisphenol A) is preferred. These compounds may be used alone or in combination of two or more. Furthermore, the polyarylate resin may contain other structural units within a range that does not depart from the spirit of this embodiment (for example, in a range of 5 mass % or less of all structural units).
[0016] The method for producing the polyarylate resin is not particularly limited, and polyarylate resins obtained by known methods can be used. Polyarylate resins obtained by interfacial polymerization and melt polymerization can be preferably used.
[0017] The weight average molecular weight of the polyarylate resin is preferably 30,000 or more, more preferably 35,000 or more, and even more preferably 38,000 or more. By setting it to the lower limit or more, the formability of the film tends to improve. In addition, the weight average molecular weight of the polyarylate resin is preferably 55,000 or less, more preferably 50,000 or less, even more preferably 46,000 or less, and even more preferably 43,000 or less. By setting the upper limit of the weight average molecular weight of the polyarylate resin to 55,000 or less, an increase in the haze of the film can be effectively suppressed.
[0018] The glass transition temperature (Tg) of the polyarylate resin is preferably 180°C or higher, more preferably 185°C or higher, and even more preferably 190°C or higher. By setting it to the lower limit or higher, shrinkage during heating can be suppressed. The upper limit of the glass transition temperature (Tg) of the polyarylate resin is not particularly specified, but is preferably 220°C or lower, more preferably 215°C or lower, even more preferably 210°C or lower, even more preferably 205°C or lower, and even more preferably 200°C or lower. By setting it to the upper limit or lower, an increase in the haze of the film can be effectively suppressed. The glass transition temperature (Tg) of the polyarylate resin is measured according to the description in the Examples section described later.
[0019] <Blend ratio of aromatic polycarbonate resin and polyarylate resin> The resin composition of the present embodiment contains 20 to 80 parts by mass of aromatic polycarbonate resin and 80 to 20 parts by mass of polyarylate resin, preferably contains 30 to 70 parts by mass of aromatic polycarbonate resin and 70 to 30 parts by mass of polyarylate resin, and more preferably contains 40 to 60 parts by mass of aromatic polycarbonate resin and 60 to 40 parts by mass of polyarylate resin. The blend ratio of aromatic polycarbonate resin and polyarylate resin can be appropriately adjusted depending on the application. By making the content of aromatic polycarbonate resin larger than the content of polyarylate resin, the fluidity is increased, so that foreign matter can be removed by a filter. By making the content of polyarylate resin larger than the content of aromatic polycarbonate resin, shrinkage during heating can be suppressed. In this embodiment, it is particularly preferable that the above range is satisfied when the total amount of the aromatic polycarbonate resin and the polyarylate resin is taken as 100 parts by mass.
[0020] The total amount of the aromatic polycarbonate resin and the polyarylate resin in the resin composition of this embodiment is preferably 90 mass % or more, more preferably 95 mass % or more, and even more preferably 99 mass % or more in the resin composition. The aromatic polycarbonate resin and the polyarylate resin may each be contained in a single type or in a combination of two or more types. When two or more types are contained, the total amount is preferably within the above range.
[0021] <Metal salts of phosphate compounds> The resin composition of the present embodiment contains a metal salt of a phosphate compound. By using the metal salt of a phosphate compound, it is possible to effectively suppress roll contamination even when an alloy of an aromatic polycarbonate resin and a polyarylate resin is formed into a film. The metal constituting the metal salt of the phosphate compound is exemplified by sodium and zinc, and zinc is preferred. That is, the resin composition of the present embodiment preferably contains a zinc salt of a phosphate compound. When the zinc salt of a phosphate compound is used, the effect of the present invention tends to be more effectively exhibited.
[0022] In this embodiment, the metal salt of the phosphate compound preferably contains at least one of a compound represented by formula (P1) and a compound represented by formula (P2). Formula (P1) Formula (P2) [ka] (In formula (P1) and formula (P2), R x each independently represents a linear or branched alkyl group having 3 to 30 carbon atoms. R x The number of carbon atoms in the alkyl group is preferably 8 or more, more preferably 13 or more, and even more preferably 15 or more, and is still more preferably 25 or less, even more preferably 20 or less, and most preferably 18. R x is a straight-chain or branched alkyl group, but is preferably a straight-chain alkyl group.
[0023] In this embodiment, it is more preferred that the metal salt of the phosphate compound comprises at least one of the compounds represented by formula (P1-1) and (P2-1).In this embodiment, it is more preferred that the mixture of the compounds represented by formula (P1-1) and (P2-1) is used. Formula (P1-1) Formula (P2- 1 ) [ka]
[0024] In the resin composition of this embodiment, the content of the metal salt of the phosphate compound relative to 100 parts by mass of the aromatic polycarbonate resin and the polyarylate resin is preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, and even more preferably 0.03 parts by mass or more. By making it equal to or more than the lower limit, the occurrence of roll stains can be effectively suppressed. The content of the metal salt of the phosphate compound relative to 100 parts by mass of the aromatic polycarbonate resin and the polyarylate resin is preferably 0.15 parts by mass or less, more preferably 0.10 parts by mass or less, even more preferably 0.08 parts by mass or less, and even more preferably 0.07 parts by mass or less. By making it equal to or less than the upper limit, the occurrence of roll stains can be effectively suppressed.
[0025] In addition, the resin composition of this embodiment may contain a phosphate compound that is not substituted with a metal salt, as long as the effect of this embodiment is not significantly deviated from. However, it is preferable that the resin composition of this embodiment does not substantially contain a phosphate compound that is not substituted with a metal salt. "Substantially not containing" means that the content of the phosphate compound that is not substituted with a metal salt is 10% by mass or less of the content of the metal salt of the phosphate compound contained in the resin composition of this embodiment, preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.1% by mass or less. By adopting such a configuration, the effect of suppressing the dirt on the roll tends to be more effectively exhibited.
[0026] <Release agent> The resin composition of the present embodiment preferably contains a release agent. By containing a release agent, a film having excellent releasability can be obtained. The release agent may be at least one compound selected from the group consisting of aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, and polysiloxane-based silicone oils, and is preferably an ester of aliphatic carboxylic acids and alcohols. Specific examples of esters of aliphatic carboxylic acids and alcohols include beeswax (a mixture containing myricyl palmitate as a main component), stearyl stearate, behenyl behenate, stearyl behenate, glycerin monopalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol distearate, pentaerythritol tristearate, and pentaerythritol tetrastearate. In addition, as the release agent, the release agents described in paragraph 0032 of JP 2017-226848 A and paragraph 0056 of JP 2018-199745 A can be used, the contents of which are incorporated herein by reference.
[0027] When the resin composition contains a release agent, the content thereof is preferably 0.001 part by mass or more, more preferably 0.005 part by mass or more, and preferably 2 parts by mass or less, more preferably 1 part by mass or less, and even more preferably 0.5 parts by mass or less, per 100 parts by mass of the total of the aromatic polycarbonate resin and the polyarylate resin. The release agent may be used alone or in combination of two or more. When two or more types are used, the total amount is preferably within the above range.
[0028] <Other ingredients> In addition to the above components, the resin composition of the present embodiment may contain other components within the scope of the present invention. Specifically, the resin composition may contain antioxidants, heat stabilizers, flame retardants, flame retardant assistants, ultraviolet absorbers, colorants, antistatic agents, fluorescent brighteners, antifogging agents, flow improvers, plasticizers, dispersants, antibacterial agents, antiblocking agents, impact improvers, sliding improvers, hue improvers, acid trapping agents, etc. These components may be used alone or in combination of two or more. The resin composition of the present embodiment is adjusted so that the total of the aromatic polycarbonate resin, the polyarylate resin, the metal salt of a phosphate compound, and the release agent and other components that are blended as necessary, is 100 mass %. The resin composition of the present embodiment may contain a phosphorus-based antioxidant, but may not contain one. The resin composition of the present embodiment preferably does not substantially contain a phosphorus-based antioxidant. "Substantially does not contain" means that the content of the phosphorus-based antioxidant is 10% by mass or less of the content of the phosphorus-based antioxidant contained in the resin composition of the present embodiment, preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.1% by mass or less. By adopting such a configuration, the effect of suppressing the staining of the roll tends to be more effectively exhibited.
[0029] <Physical properties of resin composition> The resin composition of the present embodiment is preferably excellent in heat resistance. Specifically, the glass transition temperature of the resin composition measured by differential scanning calorimetry is preferably 155°C or higher, more preferably 156°C or higher, even more preferably 157°C or higher, even more preferably 158°C or higher, even more preferably 159°C or higher, and even more preferably 160°C or higher. The upper limit of the glass transition temperature is not particularly specified, but is preferably 210°C or lower, more preferably 200°C or lower, even more preferably 190°C or lower, even more preferably 180°C or lower, and even more preferably 170°C or lower. By setting it to the upper limit or lower, the formability of the film tends to be further improved. The glass transition temperature is measured as described in the Examples section below.
[0030] The resin composition of the present embodiment preferably has excellent transparency. Specifically, the resin composition of the present embodiment has a total light transmittance of preferably 85.0% or more, more preferably 88.0% or more, and even more preferably 90.0% or more when molded into a film having a thickness of 200 μm. The upper limit of the total light transmittance is ideally 100%, but practically 98% or less. Furthermore, the resin composition of the present embodiment preferably has a haze of 1.0% or less when molded into a film having a thickness of 200 μm, more preferably 0.8% or less, even more preferably 0.5% or less, even more preferably 0.4% or less, and even more preferably 0.2% or less. The lower limit is ideally 0%, but practically 0.01% or more. The total light transmittance and haze are measured according to the method described in the examples below.
[0031] <Film> The film of the present embodiment is formed from the resin composition of the present embodiment. The film of this embodiment can be used as a monolayer film. When the film of this embodiment is a monolayer film, its thickness is preferably 25 μm or more, more preferably 30 μm or more, even more preferably 35 μm or more, even more preferably 40 μm or more, and even more preferably 50 μm or more. By making it equal to or greater than the lower limit, there is a tendency that breakage during film formation can be suppressed. In addition, the thickness of the monolayer film is preferably 500 μm or less, more preferably 400 μm or less, even more preferably 300 μm or less, even more preferably 250 μm or less, and even more preferably 200 μm or less. By making it equal to or less than the upper limit, there is a tendency that bending resistance is further improved.
[0032] The film of the present embodiment can be used as a multilayer film including the film of the present embodiment (single layer film). As the layer included in the multilayer film, in addition to the film of the present embodiment, known layers can be used. The film of this embodiment is used as a multilayer film having at least one of a hard coat layer, an antiblocking layer, an adhesive layer, an adhesion layer, and an index matching layer on one or both sides of the film. The film of this embodiment is preferably used as a transparent conductive film having a protective layer, an adhesive layer, a substrate, and an electrode layer in this order, in which at least one of the substrate and the protective layer (preferably at least the protective layer) is the film of this embodiment. The transparent conductive film is also preferably used as a transparent conductive film for use in film sensors of touch panels, electronic paper, dye-sensitized solar cells, touch sensors, and the like. For details of the multilayer film, the hard coat layer described in paragraphs 0101 to 0108 of International Publication No. 2018 / 062328, the transparent conductive layer (electrode layer) in paragraphs 0109 to 0112, the adhesive layer described in paragraphs 0125 to 0126, the conductive layer described in paragraphs 0077 to 0082 of JP-A-2020-122124, the index matching (IM) layer, hard coat layer, and anti-blocking hard coat layer described in paragraphs 0083 to 0085, the conductive layer described in paragraphs 0102 to 0105 of JP-A-2018-058233, and the description of the application of the transparent conductive film described in paragraphs 0106 and 0107 can be referred to, and the contents of these are incorporated herein by reference.
[0033] When the film of the present embodiment is a multilayer film, its thickness is preferably 25 μm or more, more preferably 35 μm or more, even more preferably 40 μm or more, even more preferably 45 μm or more, and even more preferably 50 μm or more. By making it equal to or greater than the lower limit, breakage of the film during transportation can be effectively suppressed. In addition, the thickness of the multilayer film is preferably 500 μm or less, more preferably 400 μm or less, even more preferably 300 μm or less, even more preferably 250 μm or less, and even more preferably 200 μm or less. By making it equal to or less than the upper limit, cracks during bending can be effectively suppressed. The film of the present embodiment is also preferably used for applications other than those mentioned above.
[0034] The film of the present embodiment is produced by using the resin composition of the present embodiment according to a known film production method. Preferably, the film of the present embodiment is produced by a method including extruding the resin composition of the present embodiment and conveying the extrudate through a roll to form the extrudate.
[0035] As described above, the film of the present embodiment may be a single-layer film or a multilayer film composed of a plurality of thermoplastic resin layers. A known method can also be used for the manufacturing method of the multilayer film. For example, during melt extrusion using a T-die, the multilayer film can be formed by laminating the materials inside the die and forming them into a film, or by laminating the materials after forming them into a film. EXAMPLES
[0036] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. If the measuring instruments used in the examples are difficult to obtain due to discontinuation or the like, measurements can be made using other instruments with equivalent performance.
[0037] 1. Raw materials <Aromatic polycarbonate resin (A)> A1: H-7000F, bisphenol A polycarbonate resin, manufactured by Mitsubishi Engineering Plastics Corporation, Iupilon (registered trademark), weight average molecular weight 24,900, glass transition temperature: 141°C A2: S-3000F, bisphenol A polycarbonate resin, Mitsubishi Engineering Plastics Corporation, Iupilon (registered trademark), weight average molecular weight 41,300, glass transition temperature 148°C <Polyarylate resin (B)> B1: U polymer, polyarylate resin, manufactured by Unitika Ltd., product name: U-Powder L type, carboxylic acid component: terephthalic acid / isophthalic acid = 50 / 50 mol%, bisphenol component: bisphenol A = 100 mol%, weight average molecular weight 40,800, glass transition temperature 195°C
[0038] <Metal Salts of Phosphate Compounds (C)> C1: A mixture of the following compounds, with a molar ratio of left:right=2:1. JP-518Zn, manufactured by Johoku Chemical Co., Ltd. [ka]
[0039] <Phosphate Compound (D)> D1: AX-71, ADEKA, ester exchange inhibitor [ka]
[0040] <Antioxidants (E)> E1: PEP-36, manufactured by ADEKA, phosphite-based antioxidant <Release agent (F)> F1: S-100A glycerin monostearate (Riken Vitamin Co., Ltd., Rikemal S-100A)
[0041] 2. Examples 1 to 3, Comparative Examples 1 to 3, Reference Example 1 <Production of resin pellets> The components were blended in a tumbler to obtain the composition shown in Table 1 or Table 2 below (the contents are shown in parts by mass in each table), and the blend was fed into the base of a twin-screw extruder (TEX30α, manufactured by Japan Steel Works, Ltd.) and melt-kneaded at a cylinder temperature of 280°C to produce pellets for the Examples, Comparative Examples, and Reference Examples.
[0042] <Film manufacturing> The pellets obtained above were extruded into a molten state using a T-die melt extruder consisting of a vented twin-screw extruder (manufactured by Japan Steel Works, Ltd., "TEX30α") with a barrel diameter of 32 mm and a screw L / D of 31.5 at a discharge rate of 10 kg / h and a screw rotation speed of 166 rpm, and the width of the first and second rolls was set to 1 mm, and the pellets were cooled and solidified to produce a film. The cylinder temperature was 280°C, and the die head temperature was 300°C. A film with a thickness of 200 μm was obtained.
[0043] <Method for measuring weight average molecular weight> The weight average molecular weight (Mw) of the aromatic polycarbonate resin, polyarylate resin, and resin composition was measured by gel permeation chromatography as follows. The gel permeation chromatography apparatus used was an LC-20AD system (manufactured by Shimadzu Corporation), and an LF-804 (manufactured by Shodex Corporation) was connected as the column. The column temperature was set to 40°C. The detector used was an RID-10A (manufactured by Shimadzu Corporation) RI detector. Chloroform was used as the eluent, and a calibration curve was created using standard polystyrene (manufactured by Tosoh Corporation). If the above-mentioned gel permeation chromatography apparatus, column, and detector are difficult to obtain, measurement can be performed using other apparatus having equivalent performance.
[0044] <Measurement of glass transition temperature (Tg)> The glass transition temperature (Tg) of the aromatic polycarbonate resin, polyarylate resin, and resin composition was measured by performing two cycles of heating and cooling according to the measurement conditions of differential scanning calorimetry (DSC) described below, and the glass transition temperature at the second heating cycle was measured. The intersection of the straight line extending the low-temperature side baseline to the high-temperature side and the tangent to the inflection point was taken as the starting glass transition temperature, the intersection of the straight line extending the high-temperature side baseline to the low-temperature side and the tangent to the inflection point was taken as the ending glass transition temperature, and the midpoint between the starting glass transition temperature and the ending glass transition temperature was taken as the glass transition temperature (Tg). The measurement conditions for the aromatic polycarbonate resin and the composition were as follows: measurement start temperature: 30°C, heating rate: 10°C / min, final temperature: 200°C, and temperature drop rate: 20°C / min. The measurement conditions for the aromatic polyarylate resin (B) were as follows: measurement start temperature: 30°C, heating rate: 10°C / min, final temperature: 250°C, and temperature drop rate: 20°C / min. The measurement device used was a differential scanning calorimeter (DSC, Hitachi High-Tech Science Corporation, "DSC7020").
[0045] <Roll stains> After 5 kg of raw material was consumed to manufacture the film, the rolls were visually inspected for the degree of dirt. The evaluation was carried out by five experts and judged by majority vote. A: No dirt is visible / only slightly visible (same level as reference example 1) B: More dirt can be seen than A C: Other than A and B, e.g., obviously dirty
[0046] <Measurement of total light transmittance> The total light transmittance of the obtained film was measured in accordance with ISO-13468-1 (measurement conditions: D65 light source, 10° visual field). For the measurement, a haze meter HM-150 manufactured by Murakami Color Research Laboratory was used. The total light transmittance is expressed in %.
[0047] <Haze measurement> The haze (%) of the obtained film was measured using a haze meter under conditions of a D65 light source and a 10° viewing angle. For the measurement, a haze meter HM-150 manufactured by Murakami Color Research Laboratory was used.
[0048] [Table 1] [Table 2] [Explanation of symbols]
[0049] 10 Transparent conductive film 11 Electrode layer (transparent conductive film) 12 Base material 13 Adhesive layer 14 Protective film
Claims
1. A resin composition comprising 20 to 80 parts by mass of an aromatic polycarbonate resin, 80 to 20 parts by mass of a polyarylate resin, and a metal salt of a phosphate compound, When the resin composition is molded into a film having a thickness of 200 μm, the haze is 1.0% or less; The composition contains 0.03 to 0.075 parts by mass of a metal salt of a phosphate compound per 100 parts by mass of the total of the aromatic polycarbonate resin and the polyarylate resin, The resin composition, wherein the metal salt of a phosphate compound comprises a compound represented by formula (P1) and a compound represented by formula (P2). Formula (P1) Formula (P2) 【Chemistry 1】 (In formula (P1) and formula (P2), each R x independently represents a linear or branched alkyl group having 3 to 30 carbon atoms.)
2. The resin composition of claim 1 , wherein the metal salt of a phosphate compound comprises a zinc salt of a phosphate compound.
3. The resin composition according to claim 1 or 2, wherein the polyarylate resin has a weight average molecular weight of 30,000 to 55,000.
4. The resin composition according to any one of claims 1 to 3, wherein the resin composition has a glass transition temperature of 155°C or higher as measured by differential scanning calorimetry.
5. The resin composition according to any one of claims 1 to 4, wherein the aromatic polycarbonate resin has a weight average molecular weight of 20,000 to 38,000.
6. A film formed from the resin composition according to any one of claims 1 to 5.
7. The film of claim 6, having a thickness of 25 to 500 μm.
8. A multilayer film comprising the film of claim 6 or 7.
9. 9. The multilayer film according to claim 8, having at least one of a hard coat layer, an antiblocking layer, an adhesive layer, an adhesion layer, and an index matching layer on one or both sides of the film.
10. A method for producing a film, comprising extruding the resin composition according to any one of claims 1 to 5 and transporting the extrudate through a roll to form the film.
Citation Information
Patent Citations
Light-accumulating polycarbonate resin composition and molded article of the same
JP2016028111A
Thermoplastic resin composition and molded article of the same
JP2017193659A
Transparent conductive film laminate, method for manufacturing transparent conductive film, and method for manufacturing touch sensor panel
JP2018152187A
